Parâmetros de irrigação para o feijoeiro em diferentes solos e épocas de semeadura na região central do Rio Grande do Sul - Silva, Joel Cordeiro da (2008)
Common bean is produced in the entire territory of Brazil and it is the staple food of many Brazilians. In spite of being cultivated in a variety of meteorological conditions, common bean is a plant sensitive to environmental stresses, mainly water stress. To appropriately provide the plant with water, it is necessary to study the climate of the region and the sowing times. Such information will be helpful to decide if the irrigation is recommended or not, and when recommended, its best planning. The objective of this study was to determine the most probable value of the duration of the cycle and the developmental phases, the irrigation requirements and the number of irrigations necessary for common bean cultivated during different sowing dates, considering the storage capacity of available water (CAD) of some of the main soils of the Central Region of the Rio Grande do Sul State, Brazil. The simulation of the developmental cycle was performed using thermal time units, in ten sowing dates (ES) and in each year of the meteorological database, from 1968 to 2006. Meteorological data were collected in the main meteorological station (MS) at Santa Maria - RS Irrigation was simulated for 13 soils in the surroundings of the MS, organized in six groups according to CAD and texture. In simulating the irrigation it were used four managements: 0.8, 0.7, 0.6 and 0.5 which correspond to the maximum uptake of 20%, 30%, 40% and 50% of CAD, respectively. The variation of the amount of water in the soil was calculated through daily water balance, considering the irrigation. Data obtained, such as the entire cycle duration and developmental phases, and the amount and number of irrigations, was submitted to analysis variance, tests of means comparison and analysis of probability distribution. The normal probability density function (fdp) was used to study the developmental cycle and the duration of the developmental phases. For the irrigation requirements and the number of irrigations, the gamma fdp was used in most cases, because of a best fit of the data. When it was not possible to adjust any fdp the empirical distribution was used. The developmental cycle has a variable duration with average values between 81 and 121 days, being shorter at the end of the spring growing season. The irrigation requirement and the number of irrigations were influenced by ES and soil type. The largest demand of water supply takes place at the end of the spring growing season and the smallest one in the beginning of the spring growing season and during the autumn growing season. For a likelihood of 90% the irrigation requirement varied between 32 and 143 mm and the number of irrigations between 3 and 20 times during the growing season.